The prevalence of metabolic syndrome and presumed non-alcoholic fatty liver disease in obese children at Tygerberg Hospital - Hough, Wayne (Stellenbosch : Stellenbosch University, 2016)
Thesis (MMed)--Stellenbosch University, 2016.